2007
DOI: 10.1021/pr700639t
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Phagocytosis Is Regulated by a Novel Rab-Dependent Complex in Shrimp Penaeus japonicus

Abstract: Rab GTPases are involved in phagosome formation and maturation. However, the role of Rab GTPases in phagocytosis against virus infection remains unknown. In this study, it was found that a Rab gene ( PjRab) from marine shrimp was upregulated in virus-resistant shrimp, suggesting that Rab GTPase was involved in the innate response to virus. The RNAi and mRNA assays revealed that the PjRab protein could regulate shrimp hemocytic phagocytosis through a protein complex consisting of the PjRab, beta-actin, tropomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
101
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 35 publications
3
101
0
1
Order By: Relevance
“…RacGTPases are probably best known for its role in the modulation of a wide range of cellular processes like proliferation, cell migration, cell polarization, membrane trafficking, cytoskeleton rearrangements, and transcriptional regulation [16]. Recently, the Ran [5,17], Rho [18] and Rab [19] family are found to be relevant to phagocytosis, implicating that the small GTPases may be involved in innate immunity. Moreover, Rac deletion in mice results in decreased B-cell maturation and T cell-independent antigen response [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…RacGTPases are probably best known for its role in the modulation of a wide range of cellular processes like proliferation, cell migration, cell polarization, membrane trafficking, cytoskeleton rearrangements, and transcriptional regulation [16]. Recently, the Ran [5,17], Rho [18] and Rab [19] family are found to be relevant to phagocytosis, implicating that the small GTPases may be involved in innate immunity. Moreover, Rac deletion in mice results in decreased B-cell maturation and T cell-independent antigen response [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Wu et al, the GST pull-down assays with the PjRab protein using WSSV-infected shrimp resulted the identification of three proteins VP466, tropomyosin, actin. Tropomyosin is not bound with PjRab but associate with PjRab through the interaction with two intermediate proteins VP466 and actin [22]. Our proposal of VP38-intermediate protein interaction involved in PjCaspase regulation merited to be further characterized in our future work.…”
Section: Introductionmentioning
confidence: 81%
“…The TCTP is suggested to bind to the GDP/GTP free form of Rab proteins as the structural studies of the TCTP from Schizosaccharomyces pombe, revealed that TCTPs form a structural superfamily with the Mss4/Dss4 family of proteins [30]. The Rab GTPase is shown to be involved in the phagocytic immune response against WSSV in M. japonicus through a protein complex of betaactin, tropomyosin, and VP466 of WSSV [31]. It is therefore, speculated that TCTP interacts with Rab GTase to induce phagocytosis against the virus [29].…”
Section: Discussionmentioning
confidence: 99%